PEDT-5 PREOPERATIVE MAGNETIC RESONANCE IMAGING AND INTRAOPERATIVE BLOOD LOSS IN CHILDHOOD POSTERIOR FOSSA TUMORS. (3rd December 2022) - Okamoto, Takanari; Yamanaka, Takumi; Takahashi, Yoshinobu; Takeuchi, Hayato; Tanigawa, Seisuke; Teramukai, Satoshi; Hashimoto, Naoya
Abstract: Background and Purpose: For removal of childhood posterior fossa tumors, it is important to control bleeding while internally decompressing the tumor. Evaluation of tumor vascularity by preoperative magnetic resonance imaging (MRI) is thought to be effective in predicting and controlling blood loss. In this study, we evaluated the relationship between imaging features, mainly susceptibility-weighted imaging (SWI), and the amount of intraoperative blood loss. Methods: Among childhood posterior fossa tumors operated on by the same surgeon between January 2016 and March 2022, 9 cases in which preoperative MRI data could be analyzed and total or subtotal resection was achieved were included. The SWI: intratumoral susceptibility signals (ITSS) grade, an index of tumor vascularity, was used to evaluate the association between the degree of vascularity (ITSS: 0-2 vs. ITSS: 3) and multiple factors, including intraoperative blood loss, in a univariate analysis. In addition, the intraoperative blood loss was analyzed by multivariate analysis. Results: There were 3 males and 6 females with a median age of 6 years (5-11). Seven medulloblastomas, one atypical teratoid/rhabdoid tumor, and one ependymoma were included. Univariate analysis showed that patients with higher vascularity (ITSS: 3) had significantly higher intraoperative blood loss (p=0.016) and larger tumor volume (p=0.032). In multivariate analysis with age, degree of contrast enhancement, degree of vascularity, tumor volume, and degree of tumor resection as independent variables, the degree of vascularity was not significantly associated with intraoperative blood loss (p=0.477), but only with tumor volume (p=0.036). Conclusion: Although the degree of tumor vascularity may be related to intraoperative blood loss, there was a strong correlation between the degree of vascularity and tumor volume, and multivariate analysis of intraoperative blood loss showed that only tumor volume was a significant factor. Higher tumor vascularity was associated with larger tumor volume, which may result in increased intraoperative bleeding.